Sediment data of different sites in the Ore Estuary sampled in Arpril 2015 and August 2015 - Wytze K Lenstra; Matthias Egger; Niels A G M van Helmond; Emma Kritzberg; Daniel J Conley; Caroline P Slomp (PANGAEA, 2018)
Estuarine sediments are key sites for removal of phosphorus (P) from rivers and the open sea. Vivianite, an Fe(II)-P mineral, can act as a major sink for P in Fe-rich coastal sediments. In this study, we investigate the burial of P in the Öre Estuary in the northern Baltic Sea. We find much higher rates of P burial at our five study sites (up to 0.145mol m-2 yr-1) when compared to more southern coastal areas in the Baltic Sea with similar rates of sedimentation. Detailed study of the sediment P forms at our site with the highest rate of sedimentation reveals a major role for P associated with Fe and the presence of vivianite crystals below the sulfate methane transition zone. By applying a reactive transport model to sediment and porewater profiles for this site, we show that vivianite may account for up to 40% of total P burial. With the model, we demonstrate that vivianite formation is promoted in sediments with a low bottom water salinity and high rates of sedimentation and Fe oxide input. While high rates of organic matter input are also required, there is an optimum rate above which vivianite formation declines. Distinct enrichments in sediment Fe and sulfur at depth in the sediment are attributed to short periods of enhanced input of riverine Fe and organic matter. These periods of enhanced input are linked to variations in rainfall on land and follow dry periods. Most of the P associated with the Fe in the sediment is likely imported from the adjacent eutrophic Baltic Proper. Our work demonstrates that variations in land-to-sea transfer of Fe may act as a key control on burial of P in coastal sediments. Ongoing climate change is expected to lead to a decrease in bottom water salinity and contribute to continued high inputs of Fe oxides from land, further promoting P burial as vivianite in the coastal zone of the northern Baltic Sea. This may enhance the role of this oligotrophic area as a sink for P imported from eutrophic parts of the Baltic Sea.
Supplement to: Lenstra, WK et al. (2018): Large variations in iron input to an oligotrophic Baltic Sea estuary: impact on sedimentary phosphorus burial. Biogeosciences, 15(22), 6979-6996, https://doi.org/10.5194/bg-15-6979-2018